2014
DOI: 10.3109/09513590.2014.896896
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of visfatin levels and lipoprotein lipid profiles in women with polycystic ovary syndrome undergoing ovarian stimulation

Abstract: The aim of this study was to determine serum and follicular fluid (FF) visfatin levels in age and weight-matched women with polycystic ovary syndrome (PCOS) and normally ovulating subjects undergoing controlled ovarian stimulation and correlate them with their lipid and lipoprotein levels. We included 80 PCOS women (40 lean and 40 overweight) and 80 age- and weight-matched controls, enrolled in the IVF program. In PCOS women, we determined significantly increased serum and FF visfatin as well as serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Since its discovery, some association has been established between visfatin and PCOS but with conflicting results [ 4 17 18 19 20 21 22 23 24 25 26 27 28 ]. A number of studies have reported that women with PCOS have higher visfatin levels than those in BMI-matched [ 17 21 34 35 ] or unmatched controls [ 18 36 37 38 ]. Moreover, visfatin levels in normal-weight PCOS patients has been found to be higher than those in obese controls [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, some association has been established between visfatin and PCOS but with conflicting results [ 4 17 18 19 20 21 22 23 24 25 26 27 28 ]. A number of studies have reported that women with PCOS have higher visfatin levels than those in BMI-matched [ 17 21 34 35 ] or unmatched controls [ 18 36 37 38 ]. Moreover, visfatin levels in normal-weight PCOS patients has been found to be higher than those in obese controls [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study by D _ Ikmen et al [23] was treated as multiple separate studies in our meta-analysis due to different BMI and age strategies, as were the studies of Tsouma et al [36], Farshchian et al [8] and Olszanecka-Glinianowicz et al [27]. Therefore, there were 22 studies included in this metaanalysis.…”
Section: Literature Selection and Study Characteristicsmentioning
confidence: 97%
“…One possibility is that the serum asprosin might be influenced by confounding effects through sex hormones, specific population conditions, and repeated freeze-thaw cycles. Another possibility is the multiple interactions with some other adipokines such as irusin, visfatin, and adiponectin, which are also secreted by the white adipose tissue (WAT) and associated with PCOS [25][26][27]. Meanwhile, we found that asprosin was positively correlated with PRL.…”
Section: / 16mentioning
confidence: 79%